Exsanguination From an Ulcerated, Atypical, Superficial Venous Malformation. (March 2019) - Ma, Li; Milne, Nathan; Strutton, Geoffrey; Ong, Beng Beng
Abstract : Abstract: Venous malformations (VMs) are the most common vascular malformations, and their diagnosis can be challenging. They may develop in any region of the body, with highly variable clinical presentations. Although they typically present early in life, many case reports have documented the sudden appearance of a previously unrecognized venous malformation in adulthood. Pain is the major complaint in most of the cases, and other complications include phlebolith formation and bleeding. To our knowledge, fatal hemorrhage from a VM has not previously been reported in the medical literature. We present a case of exsanguination from a previously undiagnosed lower limb superficial VM. This case stresses the importance of proper diagnosis and management of VM.